Digital game-based learning operationalization strategies - Aleksić Veljko V. (University of Kragujevac - Faculty of Pedagogy, Užice, 2019)
The paper presents a theoretical overview of digital game-based learning operationalization strategies. As digital games gradually permeated all the pores of modern society, they clearly cannot stand a side in contemporary educational practice. Three referent strategies for the successful digital game-based learning implementation are presented in the paper, each with its advantages and shortcomings. As this approach is relatively new, there still lacks a unique recommendation for the most efficient or the most successful way to implement digital games in learning process.